Blade (2006), volume 2 ebook - Guggenheim, Marc (Blade (2006), 2015)
Collects Blade (2006) #7-12. Hannibal King is back! And the fangs are sure to fly in this Lethal Weapon/Rush Hour-style team-up! Next, it's off to England as Blade seeks answers regarding his mysterious past — but all he's gotten is trouble, so now somebody's gonna pay! Guest staring Union Jack. Plus: Not a hoax! Not an imaginary story! Blade... DIES!